Novel synthesis of LaH2 and La2O3 through mechanochemistry and sintering - Satrio Herbirowo; Andika Widya Pramono; Hendrik Hendrik; Heri Nugraha; Vinda Puspasari; Agung Imaduddin; Martin C. Fatah; Eko Sulistiyo; Akhmad Herman Yuwono (South African Journal of Chemical Engineering, 2023)
Some hydrogen storage materials have been created by a mechanochemical method utilizing ball milling and hydrogen gas. This study developed a novel method for employing hydrogen gas in a ball milling process followed by sintering to dissociate La(OH)3 into La2O3 and produce LaH2. This study aimed to sinter and mill La(OH)3 in a planetary ball with hydrogen, determine the underlying sub-reaction pathways, and characterize the resultant products. The materials characterization was performed through XRD, PSA, DSC/TGA, and SEM-EDS. The rate of hydrogen pressure decrease during ball milling was from 0.0037 to 0.0049 bar/h. The longer the ball milling time, the higher the amount of LaH2. The resulting intermediate compounds after ball milling were LaH2, La, and H2O2, whose composition variations depended upon the initial hydrogen pressure and milling time. LaH2 and La2O3 were the final products following sintering, whose compositions varied depending on the intermediate compounds and their susceptibility to oxygen.